Racial/ethnic disparities in HPV-associated anogenital cancers among males in the United States (2005-2016): A population-based retrospective cohort study. Issue 28 (1st October 2022) - Villalona, Seiichi; Sukhdeo, Simone; Reinoso, Daisy; Stroup, Antoinette; Ferrante, Jeanne
Abstract : 163 Background: Among the HPV-associated cancers, research has primarily focused on understanding prevention and outcomes among females with cervical cancer. Limited data is available on health outcomes of male HPV-associated anogenital cancers, particularly among racial/ethnic minority groups. Methods: This population-based retrospective cohort study included 39, 601 males diagnosed with HPV-associated invasive penile and anorectal cancers between 2005-2016 in the North American Association of Central Cancer Registries. Outcomes included: age-adjusted incidence, late-stage diagnosis, survival, and cancer-specific mortality. We evaluated association of race/ethnicity with outcomes using multivariable logistic regression, adjusted survival curves, and Cox proportional hazard modeling, adjusting for age, insurance, residential characteristics (metropolitan/non-metropolitan, area poverty, and geographic region), stage, and treatment. Results: Hispanic and Non-Hispanic (NH) Black males had the highest age-adjusted incidence of penile and anorectal cancer, respectively. Higher odds of late-stage penile cancer were observed among NH Black (adjusted odds ratios [aOR] 1.22, 95% CI 1.07-1.39) and Hispanic males (aOR 1.17, 95% CI 1.04-1.31). Higher odds of late-stage anorectal cancer were observed among NH Black (aOR 1.25, 95% CI 1.14-1.36) and NH Other males (aOR 1.29, 95% CI 1.01-1.66). Compared to all other groups, NH Black males had the lowest cumulative and mean survival of both cancers and higher cancer-specific mortality (penile adjusted hazards ratios [aHR] 1.23, 95% CI 1.01-1.49; anorectal aHR 1.25, 95% CI 1.10-1.42). Adjusting for treatment attenuated associations but did not eliminate the observed cancer-specific mortality. Conclusions: Hispanic males had the highest incidence of penile cancer and were diagnosed at later stages than non-Hispanic (NH) White counterparts. NH Black males had the highest incidence of anorectal cancers, and regardless of anatomic site, they had the highest rates of late-stage diagnosis and mortality even when controlling for all other covariates, including treatment. The findings highlight the necessity of interventions to increase HPV vaccination rates, early detection, and treatment of anogenital cancers in males, particularly among men of color.